2021
DOI: 10.3389/fped.2021.770262
|View full text |Cite
|
Sign up to set email alerts
|

The Validity, Reliability, and Feasibility of Measurement Tools Used to Assess Sleep of Pre-school Aged Children: A Systematic Rapid Review

Abstract: Background: Sleep of pre-school aged children is important for their health and development, but there are currently no standards for measuring sleep in this age group. We aimed to examine the validity, reliability and feasibility of tools used to assess sleep of pre-school aged children.Methods: Studies were eligible for inclusion if they examined the validity and/or reliability and/or feasibility of a measurement tool used to examine sleep of pre-school aged children (aged 3–7 years). We systematically searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…To our knowledge, this is the first study to assess the acceptability and feasibility of a range of measurement tools used to examine the movement behaviours of pre-school children from the perspective of parents and carers [ 22 , 23 ]. This study used a novel methodology for the measurement field that is largely based on quantitative studies only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first study to assess the acceptability and feasibility of a range of measurement tools used to examine the movement behaviours of pre-school children from the perspective of parents and carers [ 22 , 23 ]. This study used a novel methodology for the measurement field that is largely based on quantitative studies only.…”
Section: Discussionmentioning
confidence: 99%
“…Through this, the study has highlighted practical issues and helpful insights that researchers may wish to consider when designing studies and selecting materials to use for measuring the movement behaviours of pre-school children, for example for intervention evaluation [ 63 ]. Moreover, the recruitment strategy was used to deliberately draw from groups whose views are often underrepresented in measurement literature [ 22 , 23 ]. Although this study included a small sample size, the study offers practical insights and strategies into the design of studies examining movement behaviours of pre-school children that may be generalisable through transferability; however, we will leave this at the discretion of the reader as to whether the findings apply to their group of interest [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate assessment tools are needed to better understand the relation between health outcomes and sleep timing and quality among children (Hjorth et al, 2012; Miller et al, 2018; Phillips et al, 2021). Epidemiological studies have often relied on reported sleep or heuristic algorithms developed three decades ago that require guidance from subjective sleep logs to identify sleep onset and wake‐up times (Cole et al, 1992; Sadeh et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A basic concern on the present study is on the reliability of the sleep diaries study. If there is a good control of bias, sleep diary might be acceptable for assessment of duration but not other parameters [ 2 ]. Nevertheless, there might also be an association with the phase of the outbreak in the study setting.…”
mentioning
confidence: 99%